Biochemical factors governing resistance in diploid cotton against grey mildew - SHEO RAJ; V. SRAVAN KUMAR, P.K. CHAKRABARTY, P.M. MUKEWAR (Indian Phytopathology, 2002)
Six cotton lines possessing different degrees of resistance to grey-mildew (Ramularia areola) were used to study the biochemical basis of resistance. These included one immune (G 135-49), three resistant (Desi 1, AC 24 and 30821) and a universal susceptible cultivar (AKH 4), from Gossypium arboreum besides, a susceptible cultivar Jayadhar belonging to G. herbaceum. Induced rather than constitutive levels of phenylalanine ammonia lyase (PAL), total phenol, gossypol and flavonols played crucial role in governing resistance. The magnitude of induction was invariably higher in resistant lines than in the susceptible plants. Besides, the ability of resistant plants to prevent greater loss in PAL, phenolics, proline and total sugar upon infection appeared important for resistance. Resistant plants also possessed higher levels of constitutive as well as induced tannins and constitutive proline. Amino acid and carbohydrate metabolism of the healthy and diseased plants did not directly reveal the significance of these constituents in resistance except that they were remarkably reduced as a result of infection.